Low-wage jobs: A means for employment integration of the unemployed? Evidence from administrative data in Germany and Austria - Carola Grün; Helmut Mahringer; Thomas Rhein (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2011)
Does the low wage sector serve as a stepping stone towards integration into better-paid jobs or at least towards integration of jobless people into employment? There is evidence for a 'low-wage trap' and for a high risk of low-wage earners to get unemployed, but this may also be due to sorting effects and not to low-wage work itself. The present paper contributes to this debate analysing employment spells of male low-wage earners who had been unemployed before, with methods of continuous-time event history analysis. The present data have been retrieved from two large administrative micro-data sources: the IAB employment sample (IABS) for Germany, and a combination of social security data from the Austrian Social Insurance Institutions. Two possible exits of low-wage spells are focused on: exits to higher-paid employment (upward mobility vs. persistence), and exits to unemployment ('no pay-low pay cycle'). The results show shorter spell durations in Austria, pointing to a considerably higher fluctuation and labour turnover in the Austrian labour market. The influence of individual and firm-related characteristics and of the individual unemployment history on exit probabilities and the role of duration dependence in both countries is investigated. With regard to upward mobility, no convincing evidence for 'true' duration dependence is found, at least for Germany. As to the risk of falling back into unemployment, the results suggest that even low-wage workers can accumulate job-related human capital favouring employment integration over time. – – Können Niedriglohnjobs für Arbeitslose als Sprungbrett in besser bezahlte Tätigkeiten oder zumindest als Brücke in eine dauerhafte Beschäftigungsintegration fungieren? Zwar deuten empirische Befunde auf die Existenz einer 'Niedriglohnfalle' und auf ein hohes Risiko von Geringverdienern hin, arbeitslos zu werden, aber das kann auch an Sortiereffekten liegen und nicht an Niedriglohnbeschäftigung per se. Wir möchten einen Beitrag zu dieser Thematik leisten und analysieren Beschäftigungsepisoden von männlichen Niedriglohnbeziehern, die zuvor arbeitslos gewesen waren, mit Methoden der Ereignisanalyse. Unsere Daten stammen aus zwei großen administrativen Mikro-Datensätzen: der IAB-Beschäftigtenstichprobe (IABS) und kombinierten Daten der Sozialversicherungsträger und der Arbeitsverwaltung in Österreich. Wir untersuchen zwei mögliche alternative Beendigungen von Niedriglohn-Beschäftigungsepisoden: zum einen Übergänge in besser bezahlte Beschäftigung und zum anderen Rückkehr in Arbeitslosigkeit. Die Ergebnisse zeigen, dass die Niedriglohnepisoden in Österreich kürzer als in Deutschland sind, was auf eine höhere Arbeitskräftefluktuation in Österreich hindeutet. Wir untersuchen den Einfluss von individuellen und firmenbezogenen Merkmalen und der vorhergehenden individuellen Arbeitsmarktbiographie auf die Übergangswahrscheinlichkeiten sowie den Einfluss der Dauerabhängigkeit in beiden Ländern. Im Hinblick auf die Aufstiegschancen in besser bezahlte Jobs finden wir keine überzeugende Evidenz für 'echte' negative Dauerabhängigkeit, zumindest in Deutschland. Ferner deuten unsere Befunde darauf hin, dass auch Niedriglohnbeschäftigte Humankapital akkumulieren können und somit ihr Rückkehrrisiko in Arbeitslosigkeit im Zeitverlauf vermindern können.
Keywords: J64; J63; J31; 330; unemployment dynamics; low wage; duration dependence; duration analysis; Ungeschützte Beschäftigung; Arbeitslosigkeit; Berufliche Integration; Beschäftigungseffekt; Deutschland; Österreich